Integrated study between Islamic law in crimes (Al-Jinaie Al Islami) and modern secular under the Malaysian Penal Code - Mohamad Yunus, Mohamad Ismail (Malayan Law Journal Sdn. Bhd., 2019)
Integrated study is about achieving holistic understanding of complex social-legal issues and problems. It is driven by the need to improve understanding about certain issues and to improve resources management by using the results of integrated research processes. Thus, this article will focus on the method of integrated legal research between Islamic law and modern secular law in the codification of law of crimes (Penal Law). In brief, Islamic law (Al-Shariah) is defined as the laws of Islam in any recognised madhhab or school of laws. Therefore, Islamic law is the basis of all the legislation and the courts have the duty of interpreting and applying the Islamic law. In doing so courts will refer to the primary sources of the Islamic law, that is the Holy Quran and the Sunnah and the subsidiary sources that is legislation, the views of the jurists, the decision of the courts and the legal opinions of the jurists. Islamic law was revealed gradually more than one thousand and four hundred years ago and consists of a complete system of life that is compatible for human being of all ages. The revelation from Allah (God) and the teachings of the Prophet Muhammad, peace be upon him (pbuh) are not only confined to the belief moral systems, but also include laws that are suitable to be implemented by mankind. The Penal Code of Malaysia is modeled under the Indian Penal Code (Act XLV of 1860), which was drafted by the Indian Law Commission. The British connection with Malaysia began through trading ventures, which was entirely nonpolitical, and it so continued until 1684 through its East India Company from which date until 1762, it was a mixed political and commercial connection.